Untwine : a novel - Danticat, Edwidge, 1969- (Scholastic Press, 2015)
Identical twin teenagers Giselle and Isabelle Boyer have always been inseparable, and expected to stay that way even though their Haitian American parents are separating--but when the entire family is caught in a car crash, everyone's world is shattered forever.